2011
DOI: 10.1136/bcr.05.2011.4178
|View full text |Cite
|
Sign up to set email alerts
|

Acute, simultaneous tear of patellar tendon and ACL: possible mechanism of injury and rationality of the two-stage surgical treatment

Abstract: BACKGROUNDPatellar tendon and anterior cruciate ligament (ACL) tear is an uncommon injury. Moreover, the mechanism of injury and the best surgical approach have not been established yet. We believe that case reports like ours contribute to a better understanding of the mechanism of injury and help the surgeon to decide whether to proceed in one-or twostage procedure. CASE PRESENTATIONA 47-year-old professional driver presented in the outpatient clinic of our department after sustaining an injury in his left kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…1 Ten case reports, including 17 patients, of ipsilateral simultaneous rupture of the patella tendon and ACL have been reported. [6][7][8][9][10][11][12][13][14][15][16] There was one case report of a tibial tubercle avulsion fracture and a tibial spine avulsion fracture with no rupture of the patella tendon. 17 This report outlines the unique situation when both of these fractures occur together with a patella tendon rupture and we provide a logical treatment option for this complex injury pattern.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ten case reports, including 17 patients, of ipsilateral simultaneous rupture of the patella tendon and ACL have been reported. [6][7][8][9][10][11][12][13][14][15][16] There was one case report of a tibial tubercle avulsion fracture and a tibial spine avulsion fracture with no rupture of the patella tendon. 17 This report outlines the unique situation when both of these fractures occur together with a patella tendon rupture and we provide a logical treatment option for this complex injury pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the standard ACL rehabilitation protocol emphasizes the gradual restoration of knee range of motion, closed chain exercises, and weight bearing as tolerated in the immediate post-operative phase of rehabilitation [25]. If the rehabilitation period for ACL reconstruction is delayed, the risk of loss of function and development of arthrofibrosis increases [8,25]. By delaying reconstruction of the ACL, the patient is able to appropriately rehabilitate the PT repair, assure adequate range of motion, control swelling and reduce the overall risk for arthrofibrosis when compared to a single stage repair combined procedures may increase the risk of rehabilitation-related complications as arthrofibrosis, which may require repeated closed manipulation or arthroscopic lysis of adhesions [3].…”
Section: Resultsmentioning
confidence: 99%
“…They did not discuss the reason for not reconstructing the ACL. Additionally, Koukoulias, et al [8] described a 47-year-old male who sustained a rupture of his PT, ACL, and MCL. The diagnosis of ACL rupture was missed during initial evaluation and was discovered at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1). [19][20][21][22][23][24][25][26][27][28][29] One of the 11 studies had 6 individual cases reported with 2 of the cases having a PT repair without ACL reconstruction; these 2 cases were excluded from the final analysis. 26 The final analysis had 18 cases.…”
Section: Resultsmentioning
confidence: 99%